Cetirizine versus diphenhydramine in the prevention of chemotherapy-related hypersensitivity reactions. (September 2019) - Durham, Charis G; Thotakura, Deepthi; Sager, Lauren; Foster, Jennifer; Herrington, Jon D
Objective: This study evaluated the role of cetirizine compared to diphenhydramine as premedications for patients receiving paclitaxel, cetuximab, and rituximab infusions. Historically, diphenhydramine has been linked with more sedation in comparison to cetirizine; however, it is unknown if cetirizine can replace diphenhydramine in the prevention of hypersensitivity reactions in patients receiving chemotherapy. Methods: This is a retrospective study designed to assess infusion reactions occurring in patients receiving diphenhydramine or cetirizine premedication for rituximab, paclitaxel, or cetuximab therapies. Infusion reactions were defined as various symptoms such as flushing, itching, alterations in heart rate and blood pressure, and dyspnea plus the clinical setting of a concurrent or very recent infusion. Results: A total of 207 patients were evaluated in this study with 83 patients receiving cetirizine and 124 diphenhydramine patients. Overall, the percentage of patients with at least one chemotherapy-related infusion event in the cetirizine group was 19.3% (95% CI 11.4–29.4) compared to diphenhydramine group 24.2% (95% CI 17.0–32.7), P = 0.40. Of the patients who received cetirizine and then experienced an event in the first cycle, 41.7% (95% CI 13.7–74.3) of the events were due to paclitaxel, 50.0% (95% CI 19.4–80.6) were due to rituximab, and 8.3% (95% CI 0.1–43.6) were due to cetuximab. Of the patients who received diphenhydramine and then experienced an event in the first cycle, 26.1% (95% CI 5.7–51.4) were due to paclitaxel, 73.9% (95% CI 48.6–94.3) were due to rituximab and none due to cetuximab. Conclusion: Cetirizine appears to be a viable substitute for diphenhydramine for the prevention of infusions reactions with cetuximab, paclitaxel, and rituximab infusions in adults. Prospective studies are needed to determine the efficacy and safety of cetirizine compared with diphenhydramine in the prevention of chemotherapy-related infusion reactions.